Saúde mental e maternidade : subsídios para as políticas de saúde mental no Paraná - Guedes, Aline Pinto (2012)
The gestation process, childbirth and puerperium are propitious to develop emotional disorders in different levels. This research tries to comprehend the meanings that some women attribute to maternity based on the experience of being interned in a psychiatric hospital. The treatment was necessary due to the intense mental suffering, added to psychiatric symptoms that prevented them from executing motherhood fully as well as taking care of themselves. There's a lack of political policies and programs aiming the treatment of these women and the ones that exist are not specific and prepared for treating mental health with emphasis on gender. This dissertation is based on qualitative research of descriptive transverse kind, in Qualitative Epistemology prospect, using psychoanalysis theoretical reference. Three clinical cases of women who were interned in a psychiatric hospital after a crisis of psychosis in puerperium period were presented. The procedure of Clinical research was used and intervention was included; which means that the psychological assistance included interviews, opened and semi-structured, with the patients and their husbands. The results part involves a discussion based on some analysis categories, raising the meanings that these women attribute to maternity. We observed similarities on the anxieties, conflicts and ambivalence that they felt. The mother helplessness, the worries with division between two children, the desire to work and the economical and emotional dependence on their husbands were some of the things they had in common. All of these women revealed, during gestation process, childbirth and puerperium, unconscious psychological contents and conflicts connected to childish fantasies, bringing significant suffering to them. They mentioned that they went through experiences of sexual and physical abuse as well as previous abortion that contributed to disorders during motherhood experience. When focusing on psycho-social issues involving the experience of maternity it is possible to develop a deeper knowledge on the subjective reality of these women; which contributes to a reflection on how to improve political policies related to the promotion of health, prevention and precocious intervention. We identified the importance of having some space where women have the capacity and autonomy to plan their future. The distance from their children due to treatment, brings some consequences to the connection between mother and baby. Therefore, we could assume the importance of rethinking the actions and mother-children services in a way that enables creating measures that contemplate the mental health of women considering necessary the proximity between the two health areas including the stimulation to empower groups of work and informing the population about mental health issues. It?s valid to improve the qualification of Primary Assistance services, with the creation of different prenatal and post-natal protocol for women who have had previous mental disorders or women who have psychological symptoms during gestation process. It?s evident the necessity of prioritizing the care with the carer, making motherhood of the mom when needed.